Enabling Dynamic Rescheduling in Kubernetes Environments with Kubernetes Scheduling Extension (KSE) - Carvalho Neto, Pedro Moritz de; Castro, Márcio; Siqueira, Frank (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2023)
An inefficient distribution of pods over nodes in a Kubernetes cluster environment may lead to a suboptimal scenario called node unbalancing. Problems related to scalability, reliability, availability, power consumption and use of resources may arise from this scenario. This study proposes an extension named Kubernetes Scheduling Extension (KSE) that allows the implementation of different node balancing algorithms in Kubernetes.